Adding evidence of the effects of treatments into relevant Wikipedia pages: a randomised trial. Issue 2 (20th February 2020) - Adams, Clive E; Montgomery, Alan A; Aburrow, Tony; Bloomfield, Sophie; Briley, Paul M; Carew, Ebun; Chatterjee-Woolman, Suravi; Feddah, Ghalia; Friedel, Johannes; Gibbard, Josh; Haynes, Euan; Hussein, Mohsin; et al.
Abstract : Objectives: To investigate the effects of adding high-grade quantitative evidence of outcomes of treatments into relevant Wikipedia pages on further information-seeking behaviour by the use of routinely collected data. Setting: Wikipedia, Cochrane summary pages and the Cochrane Library. Design: Randomised trial. Participants: Wikipedia pages which were highly relevant to up-to-date Cochrane Schizophrenia systematic reviews that contained a Summary of Findings table. Interventions: Eligible Wikipedia pages in the intervention group were seeded with tables of best evidence of the effects of care and hyperlinks to the source Cochrane review. Eligible Wikipedia pages in the control group were left unchanged. Main outcome measures: Routinely collected data on access to the full text and summary web page (after 12 months). Results: We randomised 70 Wikipedia pages (100% follow-up). Six of the 35 Wikipedia pages in the intervention group had the tabular format deleted during the study but all pages continued to report the same data within the text. There was no evidence of effect on either of the coprimary outcomes: full-text access adjusted ratio of geometric means 1.30, 95% CI: 0.71 to 2.38; page views 1.14, 95% CI: 0.6 to 2.13. Results were similar for all other outcomes, with exception of Altmetric score for which there was some evidence of clear effect (1.36, 95% CI: 1.05 to 1.78). Conclusions: The pursuit of fair balance within Wikipedia healthcare pages is impressive and its reach unsurpassed. For every person who sought and clicked the reference on the 'intervention' Wikipedia page to seek more information (the primary outcome), many more are likely to have been informed by the page alone. Enriching Wikipedia content is, potentially, a powerful way to improve health literacy and it is possible to test the effects of seeding pages with evidence. This trial should be replicated, expanded and developed. Trial registration number: IRCT2017070330407N2 .